Application of Non-Tax State Revenue (PNBP) to Marriage Costs in Takalar Regency - Adnan Lira (Faculty of Law, Universitas Pekalongan, 2020)
This research aims to determine the public's response to PP no. 48 of 2014 in Takalar Regency , to determine the effectiveness of PP no. 48 of 2014 on wedding costs in Takala Regency, and to find out the implications of implementing PP No. 48 of 2014 regarding wedding costs in Takalar Regency . This type of research uses a field method , namely a method that uses structured interviews . The results of this research indicate that, the presence of PP no. 48 of 2014 shows a positive response to the community ,Implementation of Government Regulation no. 48 of 2014 regarding marriage fees in Takalar Regency is considered less effective, this can be seen from the legal substance which still has issues regarding the involvement of several parties and the nominal difference in marriage fees, law enforcement which is still lacking and the community response which still uses third parties to take care of it. administration , there are three typical societies after the emergence of PP No. 48 of 2014: People who know and implement it, people who know and don't implement it, people who don't understand PP No. 48/2014